Intertextuality as a Tool for Creative Advertising - M. V. Terskikh (Научный диалог, 2019)
The article is devoted to the study of multicode intertextuality in modern advertising discourse. The relevance of the study is determined by the high interest of specialists in different areas of scientific knowledge to the problem of intertext interaction, the functioning of the intertextuality mechanism in advertising multicode discourse, as well as the fact that the advertising industry is dynamic and provides new extensive research material every day. From the author’s point of view the analysis of intertextual indices of various semiotic codes is of particular importance. This is due to the increasingly active use of not only verbal, but also iconic intertextuality in modern media discourse; high acting potential of visual and audio intertextuality; greater recognition of these codes by the recipients. The author defines creativity as a meaningful concept for advertising, suggests considering intertextuality as a category of creativity, notes the importance of using creative options for the synthesis of linguistic and visual sign systems. The article pays special attention to the pragmatic aspects of intertextuality in advertising, the functional load of verbal, visual and auditory intertextuality as a tool for producing a creative advertising. The material for the study was modern Russian advertising videos, which are based on an appeal to precedent texts. The method of intertextual analysis was used as the basic one, which consists in establishing relations of productivity between texts and analyzing the formal and semantic transformation of text units and the whole text.